Strategy for Increasing Early Childhood Literacy Skills at PAUD Ar-Rahman Benteng, Sungain Batang District, Indragiri Ilir Regency, Jambi Province - Hindun, Hindun; Rapiko, Rapiko; Rasidin, Rasidin; Siti Aisah (Green Publisher, 2024)
This research aims to examine the improvement of early childhood literacy skills by using exploratory strategies in early childhood at PAUD Ar-rahman Benteng, Sungai Batang District, Indragiri Ilir Regency, Jambi Province. Increasing early literacy skills referred to in this research is to explain children's abilities in using letters or reading and writing which are mastered before children learn how to read and write. This type of research is descriptive qualitative research because data regarding teacher strategies in introducing early childhood literacy requires a lot of qualitative data. Where the teacher is the implementer of learning while the researcher is the observer. This research is in the odd semester 2023/2024, namely in February. The subjects of this research were Ar-Rahman Benteng PAUD students, consisting of 23 students. The object of research is students' initial literacy abilities. Data collection techniques use observation, interviews and documentation. The data was analyzed using the mile and Huberman data analysis model, namely running or flowing (Flow model analysis). The analysis consisted of data collection, data reduction, data display, and verification/drawing conclusions. The results of the research show that the increase in early childhood literacy at Ar Rahman Benteng Preschool is quite good, it can be seen that when in literacy learning activities with movement and songs, children are able to read and write letter symbols that match the songs, children are able to imitate writing letters modeled by the teacher and enthusiastic about literacy activities.